Student Learning Activity Assessment Instruments in Civics Learning for Fifth Grade Elementary School - Utamiani, Ni Made; Parmiti, Desak Putu (MIMBAR PGSD Undiksha, 2022)
The problem today lies in the assessment quality related to the teacher's mechanism, procedure, or assessment instrument. The teacher assesses student learning activity only through observation without using the right assessment instrument. This study aimed to develop an instrument for assessing learning activity for students in the fifth-grade Civics Education subject in elementary school. This research belongs to the type of development research which was developed using the RDR model. The subjects involved in the study were two instrument experts. The method used to collect data is the non-test method in the form of expert validation sheets and questionnaires. The instrument used in collecting data is a questionnaire. The data obtained in the study were then analyzed using qualitative and quantitative descriptive analysis techniques. The results showed that the coefficient of content validity of the student learning activity assessment instrument in Civics subjects was 1.00 with very high validity criteria. The results of the calculation, the reliability coefficient of the instrument for assessing student learning activities in Civics subjects is 0.93 with very high-reliability criteria. So, based on these results, it can be concluded that the learning activity assessment instrument for students in Civics Class V subjects is valid and reliable, so it is suitable for use in learning.